THE ANALYSIS OF THE EFFECTIVENESS OF TAX REVENUES OF RESTAURANTS AND ENTERTAINMENT BASED ON TAX ASSESSMENT SYSTEM AND ITS CONTRIBUTION TO THE OWN-SOURCE REVENUE MANADO CITY - Lumintang, Sintia Febriani; Tinangon, Jantje; Kalalo, Meily Y.B (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
The implementation of regional autonomy in the role of own-source Revenue is expected and intended to be a buffer in financing activities of regional development. From several types of local taxes, the of concern of the Manado Government is the Restaurant and Entertainment Tax. This study was conducted to determine the level of effectiveness and contribution of Restaurant and Entertainment Tax revenues as a source of of to the city of Manado. The analytical method used is descriptive quantitative method, which analyzes the target data and actual revenues of Restaurant Tax and Entertainment Tax in 2010 to 2014 by using the ratio of the effectiveness and contribution. The results shows that the level of effectiveness of restaurant tax in 2010, 2012, 2013, and 2014 levels of effectiveness meet the criteria of highly effective and in 2011 the level of effectiveness meet the criteria of effective, entertainment tax in 2010, 2012, and 2013 meet the criteria of highly effective and in 2011 and 2014 the level of effectiveness meet the criteria of effective. Tax contributions restaurant and entertainment tax as a source of revenue over the past five years is rated not be maximum and categoried in the criteria for very poor contributions. The Manado city government should increase tax collection control function in the restaurant and entertainment taxes to increase tax contributions to local revenues in the city of Manado. Keywords: restaurant tax, entertainment tax, regional income, effectiveness